About cardinal numbers of Manchu and Mongolian: Монгол, манж хэлний үндсэн тооны нэрийн тухайд - Э.Мөнх-Учрал (Acta Mongolica, 2008)
The comparative study ofnumeral is one ofthe most important work to investigate the relationship of the Altaic languages. Thus, I pretend to focus my attention on a comparative study of the Mongolian-Manchu cardinal numerals. The cardinal numeral's main structure is: a. stem+suffix “ban” (or it's versions) b. stem+suffix “r”+suffix “ban” (or it’s versions) I think, an earlier original form of cardinal numerals can be reconstructed based on this general structure. For example, *ni-r-ben > mo. ni-gen, ma. emu. In my view, Manchu use Tibetan words for the numerals above 10000 which is definitely tranferred by Mongolian and this is demonstrate that Manchu-Tungus further Jurchen was under the deapest influence of Mongolian culture. Scholars who stand on the field of Non-Altaic theory use the numeral correnpondence of these languages to express serious doubts concerning the validity ofthe Altaic theory. As a result of my work, I concluded the greater part ofMongolian-Manchu numerals (more than 70 percent) have a genetic relationship, common structures and their evolution path is same in basically. And some of them such as Jurchen’s numeral “11 to 19“ is cause of Altaic language correspondence.